2000
DOI: 10.1161/01.atv.20.4.923
|View full text |Cite
|
Sign up to set email alerts
|

Increased Flow and Shear Stress Enhance In Vivo Transforming Growth Factor-β1 After Experimental Arterial Injury

Abstract: Abstract-We have previously demonstrated that high-flow (HF) conditions inhibit experimental intimal hyperplasia.We hypothesized that such flow conditions may alter transforming growth factor-␤1 (TGF-␤1) after mural injury. The right common carotid artery (CCA) was balloon-injured in 54 New Zealand White male rabbits. Flow was thereafter preserved (normal flow [NF]), reduced by partial outflow occlusion (low flow [LF]), or increased by ligation of the left CCA (HF). Four sham-operated animals served as uninjur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…To confirm that shear-induced remodeling did not indirectly affect axial strain, we assessed axial strain in left carotid arteries 1 week after ligation of the right carotid artery. We 7 and others 8 have shown that this procedure causes a doubling of shear stress in the left carotid artery.…”
Section: Manipulation Of Blood Flow Ratementioning
confidence: 58%
See 1 more Smart Citation
“…To confirm that shear-induced remodeling did not indirectly affect axial strain, we assessed axial strain in left carotid arteries 1 week after ligation of the right carotid artery. We 7 and others 8 have shown that this procedure causes a doubling of shear stress in the left carotid artery.…”
Section: Manipulation Of Blood Flow Ratementioning
confidence: 58%
“…To further assess possible effects of shear on axial strain, we performed ligations of the contralateral carotid artery, which causes a doubling of shear stress. 7,8 Seven days later, axial strain (60.0Ϯ7%) was not significantly different from that of control arteries (PϾ0.05). These findings indicate that changes in neither circumferential tensile stress nor shear stress can account for the rapid remodeling that normalized increases in axial strain.…”
Section: Remodeling In Response To Altered Axial Strain Was Not Due Tmentioning
confidence: 90%
“…TGF-␤1 expression was increased in 4-wk-old shunt animals relative to controls (8), which may be due in part to increased TGF-␤1 expression and release by PASMC exposed to stretch (30). Furthermore, TGF-␤1 expression was enhanced by increased flow and shear stress in vivo (31), and TGF-␤1 has been shown to up-regulate FGF-2 in vascular SMC (32). Together, these data suggest that induction of TGF-␤1 expression and release by biomechanical forces may stimulate FGF-2 expression in PASMC.…”
Section: Discussionmentioning
confidence: 93%
“…As for the fundamental mechanotransduction mechanism triggering these responses, it is still unclear exactly how the cell might sense such low levels of interstitial flow. It has been established that mechanical forces like stretch can drive fibroblast differentiation toward a myofibroblast phenotype (Arora and McCulloch, 1994;Hinz et al, 2001a;Hinz and Gabbiani, 2003b), although the mechanism remains unclear; furthermore, 2D shear stress can induce autocrine TGF-␤ 1 expression in vascular smooth muscle cells both in vitro on confluent cell monolayers (Ueba et al, 1997) or in vivo after experimental artery injury (Song et al, 2000). Here, the levels of interstitial flow imposed are extremely small: based on a measured average hydraulic conductivity of 1ϫ10 -9 cm 2 at the beginning of the experiment that decreased to 2ϫ10 -10 cm 2 after 5 days of interstitial flow owing to matrix remodeling (Ng and Swartz, 2003), we estimated the average fluid shear stress on the cells to vary between 0.15 and 0.33 dyn/cm 2 (Wang and Tarbell, 1995).…”
Section: Discussionmentioning
confidence: 99%